Decreased axon flare reaction to electrical stimulation in patients with chronic demyelinating inflammatory polyneuropathy - Kokotis, Panagiotis; Schmelz, Martin; Papagianni, Aikaterini; Zambelis, Thomas; Karandreas, Nikos (Journal of clinical neurophysiology, 2017)
Purpose: In chronic inflammatory demyelinating polyradiculopathy (CIDP), the impairment of unmyelinated nerve fibers appears unexpected. The measurement of the electrically induced axon flare reflex is a clinical test to assess the peripheral C-nociceptor function. In this study, we compared the flare area in patients suffering from CIDP with healthy subjects. Methods: We examined 18 patients fulfilling the criteria for CIDP (11 men, mean age 51.8 years, SD 15.1) and 18 age-matched adult healthy volunteers (control group) (11 men, mean age 51.9 years, SD 15.8). The flare responses were elicited by transcutaneous electrical stimulation and recorded by laser Doppler imaging. Results: There was a significant reduction of electrically induced maximum flare area in the foot dorsum of patients with CIDP (t-value 2.08, P = 0.04) which proved to be length-dependent measured by a numerical index comparing the results with the forearm and thigh. The repeatedmeasures ANOVA revealed statistically significant smaller flare areas in all body regions for the CIDP group (P < 0.001). Conclusions: The axon flare reaction to electrical stimulation was decreased in patients with chronic demyelinating inflammatory polyneuropathy. The evaluation of the axon flare response can be proposed as a noninvasive objective functional test to detect an impaired C-fiber function in CIDP patients with the advantages of simplicity of the procedure, time economy, and objectivity.